Subsidy wars and modern industrial policy - Kenneth A. Reinert (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2025)
Traditional economic nationalism, techno-nationalism and national security concerns have converged into a modern industrial policy, which is being pursued by multiple actors, including the US, China, India, Republic of Korea, and the EU. Driven by new subsidy wars, these policies pose a tremendous challenge for global economic relations.
Keywords: 330